CFBDSIR 2149-0403: young isolated planetary-mass object or high-metallicity low-mass brown dwarf? - Delorme, Philippe; Homeier, Derek (Arxiv, 2017)
We conducted a multi-wavelength, multi-instrument observational characterisation of the candidate free-floating planet CFBDSIR~J214947.2-040308.9, a late T-dwarf with possible low-gravity features, in order to constrain its physical properties. We analyzed 9 hours of X-Shooter spectroscopy with signal detectable from 0.8--2.3$μ$m, as well as additional photometry in the mid-infrared using the Spitzer Space Telescope. Combined with a VLT/HAWK-I astrometric parallax, this enabled a full characterisation of the absolute flux from the visible to 5$μ$m, encompassing more than 90% of the expected energy emitted by such a cool late T-type object. Our analysis of the spectrum also provided the radial velocity and therefore the determination of its full 3-D kinematics. While our new spectrum confirms the low gravity and/or high metallicity of CFBDSIR2149, the parallax and kinematics safely rule out membership to any known young moving group, including AB~Doradus. We use the equivalent width of the KI doublet at 1.25$\m as a promising tool to discriminate the effects of low-gravity from the effects of high-metallicity on the emission spectra of cool atmospheres. In the case of CFBDSIR2149, the observed KI doublet clearly favours the low-gravity solution. CFBDSIR2149 is therefore a peculiar late-T dwarf that is probably a young, planetary-mass object (2--13Mjup, $<$500Myr) possibly similar to the exoplanet 51Erib, or perhaps a 2--40Mjup brown dwarf with super-solar metallicity.
Gesehen am 11.10.2017